2016
DOI: 10.1111/ecc.12485
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of standardised uptake value (SUVmax ) measured on 18F-fluorodeoxyglucose positron emission tomography/computed tomography in patients with small cell lung cancer

Abstract: Certain prognostic factors for small cell lung cancer (SCLC) have been validated, but the prognostic role of 18F-FDG PET/CT still remains unclear. The aim of this study was to evaluate the prognostic significance of 18F-FDG PET/CT in patients with SCLC. We reviewed 142 patients with pathologically proven SCLC who underwent pre-treatment 18F-FDG PET/CT. Standardised uptake value (SUV ) and other potential prognostic variables were chosen for analysis. The mean age of the study population was 58.2 ± 10.1 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Many of these suggested that tumor metabolic parameters, such as SUVmax, MTV and TLG, are associated with patient prognosis [4,9,11,20,21]. In contrast, other studies have not proved that PET parameters are independent prognostic factors for SCLC patients when evaluated using pretreatment FDG PET/CT alone [22,23]. Comparing two FDG PET/CT scans performed before and after the treatment, a group of investigators in Japan demonstrated that FDG PET/CT has a potential role in identifying the therapeutic response of SCLC patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these suggested that tumor metabolic parameters, such as SUVmax, MTV and TLG, are associated with patient prognosis [4,9,11,20,21]. In contrast, other studies have not proved that PET parameters are independent prognostic factors for SCLC patients when evaluated using pretreatment FDG PET/CT alone [22,23]. Comparing two FDG PET/CT scans performed before and after the treatment, a group of investigators in Japan demonstrated that FDG PET/CT has a potential role in identifying the therapeutic response of SCLC patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…The electronic search identified 1264 articles. After excluding 29 articles in languages other than English, 268 conference abstracts, and 931 studies that did not meet the inclusion criteria based on title and abstract, and after reviewing the full text of 24 articles, 12 studies including 963 patients were eligible for inclusion in this study (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) (Fig. 1).…”
Section: Study Characteristics and Qualitative Assessmentmentioning
confidence: 99%
“…Among the 12 included studies, two studies (16,18) reported OS, one study (17) reported PFS, one study (19) reported both OS and DFS, one study (23) reported both OS and the locoregional control rate (LCR), and seven studies (15,(20)(21)(22)(24)(25)(26) reported PFS and OS. For the determination of the cut-off values for high and low SUVs, five studies (15,17,19,25,26) used the receiver operating characteristic (ROC) and seven studies (16,18,(20)(21)(22)(23)(24) used medians as the threshold values. Five studies evaluated the patients in the LD stage (15,19,20,23,26).…”
Section: Study Characteristics and Qualitative Assessmentmentioning
confidence: 99%
“…However, SUVmax of a primary lesion does not have prognostic significance in terms of survival in patients with SCLC [42]. This is because SUVmax reflects only the highest metabolic activity in the tumour and not the true tumour burden [43,44]. Further, it may not reveal the heterogeneity of the tumour and is affected by statistical noise and pixel size [45].…”
Section: Discussionmentioning
confidence: 99%